Simultaneous state and parameter estimation based actuator fault detection and diagnosis for an unmanned helicopter - Wu, Chong; Qi, Juntong; Song, Dalei; Qi, Xin; Han, Jianda (Zielona Góra: Uniwersytet Zielonogórski)
Simultaneous state and parameter estimation based actuator fault detection and diagnosis (FDD) for single-rotor unmanned helicopters (UHs) is investigated in this paper. A literature review of actuator FDD for UHs is given firstly. Based on actuator healthy coefficients (AHCs), which are introduced to represent actuator faults, a combined dynamic model is established with the augmented state containing both the flight state and AHCs.
Keywords: actuator fault detection and diagnosis; unmanned helicopter; Kalman filters; set-membership filter; adaptive scheme